Pengaruh Kecerdasan Emosional, Motivasi, Dan Artificial Intelligence Terhadap Minat Generasi Z Untuk Memilih Karier Menjadi Akuntan Publik (Studi Pada Mahasiswa Akuntansi FEB Unram) - M. Roby Agus Suhadi; Lukman Effendi (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to analyze the influence of emotional intelligence, motivation, and Artificial Intelligence on Generation Z's interest in choosing a career as a public accountant. This research uses a quantitative approach with a survey method. The sample consists of 87 students from the Accounting Study Program at the Faculty of Economics and Business, University of Mataram, determined using the Slovin formula. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression analysis. The results show that emotional intelligence, motivation, and Artificial Intelligence have a positive and significant effect on students' interest in pursuing a career as a public accountant. Motivation is the most dominant factor influencing students' career interest. Simultaneously, these variables explain 66% of students’ career interest, while the remaining 34% is influenced by other factors outside the research model.